Pengaruh Amihud, Bid-Ask Spread, Case Covid-19, Marcap, dan MTB terhadap Return Saham pada Perusahaan Financial yang Terdaftar di BEI Selama Covid 2019 (Periode Maret 2020 – Maret 2022) - Susanna Susanna; Jessica Jessica; Joceline Joceline (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research is an event study that aims to examine the stock returns and liquidity of financial companies during Indonesia's first Covid-19 case. Researchers use monthly closing price data to calculate stock returns and data related to company liquidity. The sample in this study were go public companies listed on the Indonesia Stock Exchange for the period March 2020 - March 2022. With these criteria, the samples used in this study were 26 companies. Research sampling technique using purposive sampling method. The analytical tools used in this research are descriptive statistical analysis, classical assumption test, multiple linear regression analysis and hypothesis testing. Based on the results of data analysis it can be interpreted: Amihud, Marcap, MTB have an effect on stock returns; Bid-ask spread, Covid-19 case has no effect on stock returns; Amihud, Bid-Ask Spread, Case Covid-19, Marcap and MTB have a simultaneous effect on stock returns. Keywords: Amihud, Bid-Ask Spread, Case Covid-19, Marcap, MTB, Return Saham